Tagmem pada Frasa Keripik Pisang dan Frasa Nasi Tiwul (Kajian Tagmemik) - Yeni Utami; Hasan Busri; Akhmad Tabrani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Apart from having an eclectic, universal nature, Tagmemik studies can also be used to analyze language such as the phrases